Hubungan Pola Asuh Orang Tua dengan Kemandirian Activity Daily Living (ADL) pada Anak Retardasi Mental di Sekolah SLB B C Kepanjen - Risma Larasati; Zulfikar Muhammad; Galuh Kumalasari (Caring : Jurnal Keperawatan, 2020)
The pattern of parenting with the child’s independence mental retardation can be a major factor causing children unable to do daily activities such as bathing, dressing, toileting, transfer, continence, and feeding indedependently. A child’s independence with mental retardation can affect the balance between self-care and the ability to manager or care for themselves and they really need more supervision and assistance. This method used is observational design with Cross Sectional approach. The sample in this study were parents of mentally retarded children as many as 59 respondents. The sampling technique used Purpossive Sampling with research instruments is theParenting Styles and Dimensions Questionnaire (PSDQ) questionnaire and the Katz Index. Data analysis techniques used the Spearman Rank. There is a relationship between parenting parents with the independence of daily activities in mental retardation children in the study school at SLB BC Kepanjen. With significant result (p)<0,035=(p)<0,05. Almost all parents with good parenting that is authoritative, also with the independence of children mentally retarted most of them fall into the independent category. So, it can be concluded that, a child’s mental retardation will very much depend on the parenting style of his parents and good parenting will make a good child’s independence.